2015
DOI: 10.1002/14651858.cd004123.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for chronic wounds

Abstract: In people with foot ulcers due to diabetes, HBOT significantly improved the ulcers healed in the short term but not the long term and the trials had various flaws in design and/or reporting that means we are not confident in the results. More trials are needed to properly evaluate HBOT in people with chronic wounds; these trials must be adequately powered and designed to minimise all kinds of bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0
18

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(169 citation statements)
references
References 77 publications
3
148
0
18
Order By: Relevance
“…Hyperbaric oxygen therapy (HBOT) has been demonstrated to accelerate wound healing through the resulting cellular effects of enhanced intravascular oxygen concentration and pressure . Although a positive effect on wound healing has been depicted in numerous trials, the pooled data of the Cochrane review reflected improved ulcer healing rates with HBOT in the short term but not in the long term . No studies have assessed the role of HBOT on the DHU alone .…”
Section: Methods Of Managementmentioning
confidence: 99%
“…Hyperbaric oxygen therapy (HBOT) has been demonstrated to accelerate wound healing through the resulting cellular effects of enhanced intravascular oxygen concentration and pressure . Although a positive effect on wound healing has been depicted in numerous trials, the pooled data of the Cochrane review reflected improved ulcer healing rates with HBOT in the short term but not in the long term . No studies have assessed the role of HBOT on the DHU alone .…”
Section: Methods Of Managementmentioning
confidence: 99%
“…Treatment of chronic wounds involves various approaches to protect and promote healing. These include hyperbaric oxygen therapy (HBOT) , vacuum‐assisted wound closure , low‐level laser therapy and electrical stimulation . However, results from these studies are inconsistent and reported limited success with no conclusive remark on its effect .…”
Section: Introductionmentioning
confidence: 99%
“…Absolute contraindications include doxorubicin treatment (because of cardiac toxicity), mafenide acetate treatment (because of central vasoconstriction), and untreated pneumothorax [15]. According to authors of a Cochrane review of chronic wounds, HBO 2 improved healing in the short term but not with long-term follow-up [16]. In experimental studies, HBO 2 treatment led to proliferation of bovine aortic endothelial cells and human skin fibroblasts in vitro as well as accelerated wound epithelialization and neovascularization in mouse ears [17, 18].…”
Section: Discussionmentioning
confidence: 99%